Structure and Dynamics of Curcumin Encapsulated Lecithin Micelles: A Molecular Dynamics Simulation Study - Lukman Hakim; Diah Mardiana; Urnik Rokhiyah; Maria Lucia Ardhani Dwi Lestari; Zubaidah Ningsih (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Curcumin is a natural product with potential pharmaceutical applications that can be augmented by drug delivery technology such as nano emulsion. Our study focuses on microscopic structural and dynamics response of curcumin encapsulation in micellar system with lecithin as a natural surfactant under variations of composition and temperature using molecular dynamics (MD) simulations. The results highlight the self-assembly of lecithin micelle, with curcumin encapsulated inside, from initial random configurations in the absence of external field. The variation of composition shows that lecithin can aggregate into spherical and rod-like micelle with the second critical micelle concentration lies between 0.17-0.22 mol dm−3. The radial local density centering at the micelle center of mass shows that the effective radius of micelle is indeed defined by the hydrophilic groups of lecithin molecule and theencapsulated curcumin molecules are positioned closer to these hydrophilic groups than the innermost part of the micelle. The spherical micelle is shown to be thermally stable within the temperature range of 277-310 K without a perceivable change in the spherical eccentricity. The dynamics of micelle are enhanced by the temperature, but it is shown to be insensitive to the variation of lecithin-curcumin composition within the studied range. Simulation results are in agreement with the pattern obtained from experimental results based on particle size, polydispersity index, and encapsulation efficiency.